Application of transcriptome analysis to investigate the effects of long-term low temperature stress on liver function in the tiger puffer (Takifugu rubripes) - Liu, Zhifeng; Zhu, Liguang; Wang, Xinan; Liu, Shiying; Ma, Aijun; Chang, Haowen; Sun, Zhibin; Xu, Fei; Zhao, Haichi (Frontiers in Marine Science, 2022)
The tiger puffer (Takifugu rubripes) is an important economic fish species in northern China. However, it is a warm-temperature species, and low winter temperatures can result in high mortality in aquaculture. Understanding the mechanisms of cold resistance in tiger puffers will thus provide critical information to help cope with winter cold. In this study, we performed transcriptome analysis of livers from puffer fish kept at different temperatures (18°C, 13°C, and 8°C) to identify the key pathways and genes involved in the response to low-temperature stress. We also detected serum levels of proteases, arginine, and proline to obtain further information on the response to cold adaption. Totals of 51, 942, and 195 differentially expressed genes were identified in the 18°C vs 13°C, 18°C vs 8°C, and 13°C vs 8°C groups, respectively. Pathway analysis showed that significantly enriched pathways were mainly related to digestion, metabolism, and environmental adaptation. Most genes in the pathways related to digestion and metabolism were down-regulated, while most genes in the pathways related to environmental adaptation were up-regulated. Serum levels of proteases were significantly lower in the low-temperature groups (13°C and 8°C) compared with the control group (18°C), while arginine and proline levels were significantly higher in the 8°C group compared with the other two groups. These results suggest that low temperature caused digestive and metabolic disorders, as well as adaptive changes to low temperature in tiger puffers. On this premise, we found that some up-regulated genes in the pancreatic secretion pathway, arginine and proline metabolism pathway, and circadian rhythm pathway played important roles in the survival, growth, and development of tiger puffers under low-temperature stress. The accumulation of arginine and proline can maintain metabolism and circulation and resist cold stress. The circadian rhythm is closely related to digestion and metabolism, which is an adaptive change and plays a positive role in the resistance to low temperature. The results of this study provide new insights and a theoretical basis for the study of cold tolerance in tiger puffers.